Medication Safety in Hospital (International Current Pharmaceutical Journal, 2016)
The World Health Organization has recommended the adoption of basic applications in healthcare facilities to enhance medication safety over the years, but it remains unclear if these recommendations are adhered to by hospitals. We assessed the availability of primary medication safety practices in Saudi Arabian hospitals. Survey were carried out in 70 hospitals to identify the presence of core medication safety practices in Saudi Arabian hospitals and revealed that there were room and opportunity for improvement, even for cheap interventions. According to the study, only about 29% of the Saudi Arabian hospitals had a proper functioning drug safety committee, and 10% had a designated medication safety officer. It was also revealed that only 32% of the hospitals had the list of LASA authorized drugs, and 51% had a list of error-prone abbreviations and medical terms. Saturated electrolytes were also found as floor stock in 60% of all hospitals.Alreshidi, International Current Pharmaceutical Journal, December 2016, 6(1): 6-8http://www.icpjonline.com/documents/Vol6Issue1/02.pdf